2014
DOI: 10.1016/j.jpubeco.2014.05.002
|View full text |Cite
|
Sign up to set email alerts
|

“Do the right thing:” The effects of moral suasion on cooperation

Abstract: The use of moral appeals to a¤ect the behavior of others is pervasive (from the pulpit to ethics classes) but little is known about the e¤ects of moral suasion on behavior. In a series of experiments we study whether moral suasion a¤ects behavior in voluntary contribution games and the mechanisms by which behavior is altered. We …nd that observing a message with a moral standard according to the golden rule or, alternatively, utilitarian philosophy, results in a signi…cant but transitory increase in contributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(41 citation statements)
references
References 45 publications
1
40
0
Order By: Relevance
“…Then we investigate whether the positive effect of moral nudges is limited to the choice immediately after the nudge, or persists to a subsequent interaction. In this study we focus only on altruistic behaviour for two reasons: first, Dal Bó & Dal Bó 33 have already shown that a similar moral nudge persists over time in a repeated PD; second, Study 1 and Study 2 suggest that our moral nudges work similarly in the PD and the DG, therefore, although we cannot logically infer that our moral nudges equally persist to a second round both in the DG and in the PD, we expect no major differences. And, moreover, we focus only on the "personal" norm since, as shown in Studies 1 and 2, the "social" norm gives rise to similar results.…”
Section: Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Then we investigate whether the positive effect of moral nudges is limited to the choice immediately after the nudge, or persists to a subsequent interaction. In this study we focus only on altruistic behaviour for two reasons: first, Dal Bó & Dal Bó 33 have already shown that a similar moral nudge persists over time in a repeated PD; second, Study 1 and Study 2 suggest that our moral nudges work similarly in the PD and the DG, therefore, although we cannot logically infer that our moral nudges equally persist to a second round both in the DG and in the PD, we expect no major differences. And, moreover, we focus only on the "personal" norm since, as shown in Studies 1 and 2, the "social" norm gives rise to similar results.…”
Section: Studymentioning
confidence: 99%
“…While previous research has consistently found that moral nudges and, more generally, normbased policy interventions persist at least for some time 33,[36][37] , there is a lot of uncertainty concerning their spillover effect across contexts. More specifically, to the best of our knowledge, no study has explored spillover effects in the domain of simple moral nudges as the ones we explore in this work.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If explicitly faced with information about the behaviour of out-group members, might these individuals change their behavioural strategy from conformist to counter-conformist? This research can contribute to the emerging stream of literature using moral suasion to encourage pro-social behaviours (Brañas-Garza, 2007;Ferraro & Miranda, 2013;Dal Bó & Dal Bó, 2014;Bonan, Cattaneo, d'Adda & Tavoni, 2019;Bott, Cappelen, Sørensen & Tungodden, in press;Capraro et al, in press).…”
Section: Discussionmentioning
confidence: 80%
“…Unlike commonly assumed in the punishment literature, the authors observe that participants favor post hoc redistribution rules over purely punitive rules. As in Dal B o and Dal B o (2014), rules incorporate communication elements in the form of appeals to moral sentiments rather than simple peer-to-peer appeals to contribution. Finally, as anticipated in Hoffmann et al (2013), participants prefer to moderate feelings of resentment by choosing rules that provide information about aggregated rather than about individual contributions.…”
Section: Forewordmentioning
confidence: 99%